Pengaruh Kualitas Pelayanan terhadap Kepuasan Pasien BPJS di Poli Umum Puskesmas Simomulyo Surabaya - Rachel Theresia Stephanie S; Minarni Wartiningsih; Hendera Henderi (Pusat Riset dan Inovasi Nasional, 2026)
Service quality is an important factor in health service delivery because it affects patient satisfaction. BPJS patient satisfaction is an indicator of the success of Puskesmas services and reflects service quality, particularly in terms of structure and process. In general, this study aims to analyze the effect of service quality on BPJS patient satisfaction at the Simomulyo Surabaya Puskesmas General Clinic. More specifically, this study aims to identify service quality based on the dimensions of structure and process, measure the level of BPJS patient satisfaction, and analyze the influence of each dimension of service quality on patient satisfaction. This study used a quantitative observational design with a cross-sectional approach. The population consists of all BPJS patients at the Simomulyo Surabaya Community Health Center General Clinic in 2025, totaling 4,412 patients. The sample consisted of 98 respondents calculated using the Slovin formula with simple random sampling technique. Data were collected using a service quality and patient satisfaction questionnaire based on Donabedian's theory, and data analysis was performed using simple linear regression tests. Service quality was rated as good, with an average score of 3.49 for both the structure and process dimensions. BPJS patient satisfaction was also rated as good, with an average score of 3.42. There is a significant influence between the structure dimension and patient satisfaction (p-value 0.000 < 0.05) and the process dimension and patient satisfaction (p-value 0.000 < 0.05). Service quality has a significant effect on BPJS patient satisfaction at the Simomulyo Surabaya Community Health Center General Clinic. Further research is recommended to examine other dimensions of service quality, and the Community Health Center is expected to improve service quality to increase BPJS patient satisfaction.